The Impact of Legislation on Credit Risk-Comparative Evidence From the United States, the United Kingdom and Germany - Schmieder, Philipp (IMF Working Papers; Working Paper ;, 2011)
This study investigates the link between bankruptcy and security legislation and potential credit losses faced by banks based on a cross-country study for the United States (US), the United Kingdom (UK) and Germany. Focusing on corporate credit, we find that legislation produces the highest credit risk in the US, followed by Germany, while UK law is found to be most favorable for banks. US banks gains from the higher number of informal restructurings (without losses) but lose from the low level of recovery in formal proceedings. German banks demand more credit risk mitigants than UK and US banks do, but still recover less than do UK banks. To be at par with UK banks, US banks would have to recover more than twice as much in formal proceedings, while German proceedings would have to be shortened by about one half.